Experimental and numerical analysis of piezoelectric active repair of edge-cracked plate - Abuzaid, Ahmed; Hrairi, Meftah; Shaik Dawood, Mohd. Sultan Ibrahim (Sage Publishing, 2018)
This article proposes an alternative model for active repair for an edge-cracked plate with adhesively bonded piezoelectric actuator. It computes the Mode-I stress intensity factor (SIF) produced by the piezoelectric actuators using appropriate derived geometrical weight functions. Furthermore, this article presents an experimental study to verify the proposed analytical model and the finite element analysis using ANSYS software. Therefore, the analytical, finite element and experimental results for Mode-I opening of the crack conditions are demonstrated. Parametric analysis to understand the influence and to study the efficiency of the piezoelectric actuator on mitigation of the Mode-I SIF was conducted. The obtained analytical solution is applicable in the calculation of Mode-I SIF with reasonable accuracy. The result indicated that the maximum reduction of SIF is achieved with the application of high external voltage and thin thickness actuator. The relative errors of the analytical model and the experimental results are less than 10% in all the cases studied in this article.